2016
DOI: 10.1136/bmjopen-2015-008376
|View full text |Cite
|
Sign up to set email alerts
|

Metformin versus placebo in combination with insulin analogues in patients with type 2 diabetes mellitus—the randomised, blinded Copenhagen Insulin and Metformin Therapy (CIMT) trial

Abstract: ObjectiveTo assess the effect of metformin versus placebo both in combination with insulin analogue treatment on changes in carotid intima-media thickness (IMT) in patients with type 2 diabetes.Design and settingInvestigator-initiated, randomised, placebo-controlled trial with a 2×3 factorial design conducted at eight hospitals in Denmark.Participants and interventions412 participants with type 2 diabetes (glycated haemoglobin (HbA1c) ≥7.5% (≥58 mmol/mol); body mass index >25 kg/m2) were in addition to open-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 37 publications
2
55
0
Order By: Relevance
“…Our study adds to this research by showing a significant increase in leucine/isoleucine in participants with Type 2 diabetes mellitus, in both cross‐sectional observational and longitudinal randomized data analyses. This increase occurred despite the metformin‐treated group achieving better glucose control, showing less weight gain and needing a lower dose of insulin than the placebo‐treated participants . This is in line with Walford et al .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our study adds to this research by showing a significant increase in leucine/isoleucine in participants with Type 2 diabetes mellitus, in both cross‐sectional observational and longitudinal randomized data analyses. This increase occurred despite the metformin‐treated group achieving better glucose control, showing less weight gain and needing a lower dose of insulin than the placebo‐treated participants . This is in line with Walford et al .…”
Section: Discussionsupporting
confidence: 85%
“…Changes in clinical and laboratory variables from baseline to follow-up and differences between the randomized groups have been described previously [15]. Briefly, systolic and diastolic BP decreased in both groups, and a significant decrease in heart rate was observed in the placebo group compared with the metformin group.…”
Section: Changes In Clinical Variables From Baseline To Follow-upmentioning
confidence: 89%
“…These mechanisms have been studied in experimental systems, and their clinical relevance remains to be determined. To date, some but not all studies have demonstrated evidence of reduced atherosclerotic burden in type 2 diabetes patients receiving metformin . One of these, the REducing With MetfOrmin Vascular Adverse Lesions in Type 1 Diabetes (REMOVAL) study, demonstrated a minor and transient reduction for metformin vs placebo of one measure of carotid atherosclerosis in people with type 1 diabetes with cardiovascular risk factors during 3 years of randomized treatment …”
Section: Cardiovascular Protection With Metforminmentioning
confidence: 99%
“…Data from a large placebo-controlled clinical trial indicated that patients with obesity and uncontrolled T2DM treated with insulin plus metformin versus insulin plus placebo required significantly less insulin therapy and gained less weight. 60 If metformin is not tolerated and/or is contraindicated in the particular patient, another option is to use basal insulin therapy plus a GLP-1 agonist or SGLT-2 inhibitor to help offset insulin-induced weight gain.…”
Section: Pharmacological Comanagement Of Obesity and Its Metabolic Sementioning
confidence: 99%